Modern Clinical Molecular Techniques - Hu, Peter; Hegde, Madhuri; Lennon, Patrick Alan (Springer New York : Imprint: Springer, 2012)
This timely book covers the need to know clinical practices for all those involved in molecular laboratory science. The field of molecular medicine is evolving at an astounding speed. Propelled by the new insights and technologies, advances are being made at an unprecedented rate. With dual measure given to today's breakthroughs, this book is a collection of the most current practices relevant to the clinical molecular laboratorian. It begins with an introductory section on techniques and procedure.  It then presents four separate sections on infectious disease, oncology, pre/post-natal, and identity testing, with specific chapters clearly outlining clinical protocols used in daily practice. Modern Clinical Molecular Techniques cuts to the heart of what is essential for the practicing molecular laboratory scientist. It is an outstanding resource for those operating within or looking to set up a clinical molecular laboratory.